Graphene-based Materials Used as the Catalyst Support for PEMFC Applications. (2015) - Marinoiu, Adriana; Teodorescu, Constantin; Carcadea, Elena; Raceanu, Mircea; Varlam, Mihai; Cobzaru, Claudia; Stefanescu, Ioan
Abstract: Taking into consideration their high surface area, high conductivity, unique graphitized basal plane structure and potential low manufacturing cost, graphene nanocomposites such as Pt/graphene nanocomposites have been investigated as catalyst support for PEMFC applications. All materials were synthesized through a simple method of chemical oxidation and graphite oxide exfoliation, and results were confirmed by characteristic analysis. The structure, morphology and properties were characterized by using X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and thermogravimetric analysis. The XRD pattern clearly showed the complete disappearance of C(200), indicating the formation of graphene which was also confirmed by SEM images Also, an important information about the Pt/graphene nanocomposite has been obtained from chemical and thermogravimetric analysis. The chemical analysis indicates the fact that the Pt/graphene nanocomposite has the following chemical composition: C = 49.79%wt., O = 17.37%wt., H = 4.77%wt., S < 0.005%wt. and N = 3.53%wt.Pt/graphene nanocomposites are more adequate to form composite membranes for PEMFC applications than simple graphene nanocomposites.